Pengaruh Literasi Membaca dan Dampaknya Pada Kemampuan Membaca Siswa di SD Negeri Sidakaton 5 Tegal - Budiana, Nurchalistiani; Nurbaeti, Rizki Umi; Nisa, Hany Uswatun (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine whether the literacy approach can affect reading skills in fourth grade students of SD Negeri Sidakaton 5 Tegal. This research approach is quantitative with a Quasi Experimental Design (QED) design. The population of this study were all students IV of SD Negeri Sidakaton 5 Tegal totaling 67 students. The distribution is as follows: 20 students for class IV A, 27 students for class IV B and 20 students for class IV C. Sampling was done by sampling technique, namely random sampling. Data collection techniques used were pretest and posttest. The data analysis technique used is the normality test, homogeneity test and t test. The results showed that there was an effect of literacy on reading skills in fourth grade students of SD Inpres 12, Sorong Regency. This is shown by the tcount value of 13,220 with dk=n-2 (40-2=38) obtained ttable 2,024. Based on the results of value data analysis, namely tcount > ttable (13,220 > 2,024), the hypothesis is accepted